Determining Factors in Improving Employee Performance at PT. Rubber Hock Lie Sunggal Medan - Yovie Ernanda; Andri Sevendi Tamba; Klementina Situmorang; Mita Ganda Putri Pardede; Ronauli Saragi (International Journal of Applied Finance and Business Studies, 2022)
The purpose of this study was to examine and analyze the effect of motivation, satisfaction, and work discipline on employee performance at PT Rubber Hock Lie Sunggal Medan. This research is descriptive and explanatory. The population in this study was employees who found 166 people, and the sample found 117 respondents. The method in this study is quantitative. Data collection techniques used are interviews, questionnaires, and documentation studies. The data used are primary data and secondary data. Then the data is processed using the IBM SPSS Statistics application. The results of this study prove that motivation, satisfaction, and work discipline simultaneously have a positive and significant effect on employee performance at PT Rubber Hock Lie Sunggal Medan and partial motivation have no significant effect on employee performance, while job satisfaction and discipline have a positive and significant effect on employee performance at PT Rubber Hock Lie Sunggal Medan.